2000
DOI: 10.1073/pnas.050015797
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction by a nondissociable heterotrimeric yeast G protein

Abstract: Many signal transduction pathways involve heterotrimeric G proteins. The accepted model for activation of heterotrimeric G proteins states that the protein dissociates to the free G␣ (GTP)-bound subunit and free G␤␥ dimer. On GTP hydrolysis, G␣ (GDP) then reassociates with G␤␥ [Gilman, A. G. (1987) Annu. Rev. Biochem. 56, 615-649]. We reexamined this hypothesis, by using the mating G protein of the yeast Saccharomyces cerevisiae encoded by the genes GPA1, STE4, and STE18. In the absence of mating pheromone, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 13 publications
4
23
0
Order By: Relevance
“…Some studies have indicated that conformational changes within the heterotrimeric G protein (1316) rather than subunit dissociation per se are sufficient to reveal distinct effector interacting surfaces (reviewed in 12). This model is also supported by chemical (17) and molecular (18) cross-linking studies that showed physically tethered heterotrimers are still functional. Two recent studies appear to support the original hypothesis (19, 20), although matters are made more complicated by evidence that both scenarios are operative (21, 22).…”
Section: G Protein–coupled Receptors and G Protein Signalingmentioning
confidence: 63%
“…Some studies have indicated that conformational changes within the heterotrimeric G protein (1316) rather than subunit dissociation per se are sufficient to reveal distinct effector interacting surfaces (reviewed in 12). This model is also supported by chemical (17) and molecular (18) cross-linking studies that showed physically tethered heterotrimers are still functional. Two recent studies appear to support the original hypothesis (19, 20), although matters are made more complicated by evidence that both scenarios are operative (21, 22).…”
Section: G Protein–coupled Receptors and G Protein Signalingmentioning
confidence: 63%
“…The readout of experiments with RET donor and acceptor molecules fused to Gα and Gγ subunits indicates that G protein activation upon ligand binding to the receptors does not lead to dissociation, but implies a conformational change with rearrangement, reorientation, of its subunits [21,22]. Levitzki and collaborators already advanced this interpretation after finding successful signal transduction of a yeast pheromone receptor with fused G protein subunits [23]. Levitzki was also first to suggest that G proteins form stable complexes with AC being independent of the activation state of G proteins, mostly based upon co-purification of AC from turkey erythrocyte membranes (reviewed in ref.…”
Section: Setting the Stage For The Gpcr Heterotetramer: Pre-coupling mentioning
confidence: 99%
“…However, a lot of studies suggest that GPCR-G protein interaction occurs before the activation process ( [Frank et al, 2005,Galés et al, 2005,Klein et al, 2000). Indeed, an alternative hypothesis proposed that G protein could be preassembled with inactive GPCRs (Nanof et al, 1991;Nanof and Stiles, 1993).…”
Section: Gpcr-g Protein Preassemblymentioning
confidence: 99%